2009
DOI: 10.1097/dad.0b013e3181930d93
|View full text |Cite
|
Sign up to set email alerts
|

Eruptive Syringoma of the Penis. A Report of 2 Cases and a Review of the Literature

Abstract: Syringoma exclusively located to the penis is an extraordinary rare dermatological condition, and only 6 patients with syringoma exclusively located to the penis have been published previously. Light microscopical examination of routine hematoxylin and eosin-stained sections from punch biopsies with adequate depth from 2 patients was performed. Classical syringoma was diagnosed. The lesions occurred in an eruptive fashion in both patients on the dorsal and lateral aspects of the penis shaft. There was a variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…On histologic examination, syringomas are easily recognizable by the presence of comma-or tadpole tail-shaped sweat ducts in the dermis. 2 Even though syringoma lesions are benign, they may be cosmetically distressing for patients. Treatment options, mostly based on small case series and case reports, include surgical excision, electrodessication and curettage, chemical peels, cryosurgery and laser therapy.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…On histologic examination, syringomas are easily recognizable by the presence of comma-or tadpole tail-shaped sweat ducts in the dermis. 2 Even though syringoma lesions are benign, they may be cosmetically distressing for patients. Treatment options, mostly based on small case series and case reports, include surgical excision, electrodessication and curettage, chemical peels, cryosurgery and laser therapy.…”
mentioning
confidence: 99%
“…1 Rarely, syringomas can occur in extraocular sites, including the neck, axilla, breasts, lower abdomen, thighs and groin. 2 The risk factors for syringomas are unknown. Some investigators have suggested that syringomas may be caused by hormonal factors 3 or may be a reactive response to friction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An exact pathogenesis of syringoma is still unknown, but the neoplastic process, reactive hyperplasia, an association with hormonal factors is considered to be an etiologic factor2,3. Eruptive syringomas consist of the successive development of multiple papules in a limited area were thought to be a reactive process4.…”
mentioning
confidence: 99%
“…The differential diagnosis of penile syringomas includes genital warts, lichen planus, bowenoid papulosis, angiokeratoma, angiofibroma, granuloma annulare, lichen nitidus, sarcoidosis, pearly penile papules, calcinosis cutis, and so on3.…”
mentioning
confidence: 99%